2014
DOI: 10.1007/s10646-014-1369-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace concentrations of imazethapyr (IM) affect floral organs development and reproduction in Arabidopsis thaliana: IM-induced inhibition of key genes regulating anther and pollen biosynthesis

Abstract: Understanding how herbicides affect plant reproduction and growth is critical to develop herbicide toxicity model and refine herbicide risk assessment. Although our knowledge of herbicides toxicity mechanisms at the physiological and molecular level in plant vegetative phase has increased substantially in the last decades, few studies have addressed the herbicide toxicity problematic on plant reproduction. Here, we determined the long-term (4-8 weeks) effect of a chiral herbicide, imazethapyr (IM), which has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Thus, an application of ALS-inhibiting gametocides on model plant A. thaliana to replace manual emasculation will be of interest to geneticists when they wish to make many genetic crosses. The results of the present study, combined with previous studies [1214, 23, 24], suggest the possible use of other sulfonylurea chemicals as gametocides for cruciferous plants. The alternate use of other gametocides can resolve the concerns of insensitivity to tribenuron-methyl in some special genotypes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, an application of ALS-inhibiting gametocides on model plant A. thaliana to replace manual emasculation will be of interest to geneticists when they wish to make many genetic crosses. The results of the present study, combined with previous studies [1214, 23, 24], suggest the possible use of other sulfonylurea chemicals as gametocides for cruciferous plants. The alternate use of other gametocides can resolve the concerns of insensitivity to tribenuron-methyl in some special genotypes.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study also reported that a foliar spray of 15 ng of tribenuron-methyl per plant of A. thaliana had a gametocidal effect [23]. In addition, exposure to trace concentrations of imazethapyr, an ALS-inhibitor, had unstable gametocidal effects on Brassica plants [13] and affected floral organ development and reproduction in A. thaliana [24]. Thus, an application of ALS-inhibiting gametocides on model plant A. thaliana to replace manual emasculation will be of interest to geneticists when they wish to make many genetic crosses.…”
Section: Discussionmentioning
confidence: 99%
“…Petal, anther, and pollen deformations have been reported for Brassica spp. flowers exposed to low doses of glyphosate (Londo et al 2014), and anther malformations and pollen quality reductions have been reported for imazethapyr (Qian et al 2015). Malformations including reduced disk diameter ( Tanacetum vulgare , Leucanthemum vulgare ) and ray floret length ( L. vulgare ) following application of drift relevant doses of glyphosate have been documented for 2 nontarget Asteraceae species (Strandberg et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of primary sensing of xenobiotic structures, which have been characterized in animal cells, have however remained elusive in the case of plant cells (Ramel et al, 2012), even if various situations of plant-xenobiotic interactions suggest that such primary sensing may also exist in plant cells (Ramel et al, 2012). Qian et al (2015aQian et al ( , 2015b have shown that low levels of imazethapyr induced major metabolic and molecular changes in flowers or in roots. However, these imazethapyr treatments were carried out at IC50 concentrations yielding some level of toxicity.…”
Section: Characterization Of Regulatory-protein Mutations That Interfmentioning
confidence: 99%